Diversifikasi Pembiayaan Sebagai Upaya Peningkatan Profitabilitas di Bank Syariah - Maulida Masruroh (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This study examines the effect of diversification of financing based on type of contract, type of usage, and economic sector to the profitability at the Islamic bank. Diversification of financing proxied by Hirchman Herfindahl Index (HHI), and the profitability proxied by Return on Assets (ROA) was measured using the distribution of pre-tax profit to average total assets. This study uses secondary data obtained from the publication of the report the Financial Services Authority (OJK) in the period January 2013 to December 2017. The data analysis technique used in this research is multiple linear regression. The results of this study are partially diversification of financing based on type of contract does not affect the ROA at the Islamic bank, diversification of financing based on type of usage has a positive and significant effect to ROA at the Islamic bank., and diversification of financing based on economic sector has a negative and significant effect to ROA at the Islamic bank.. While simultaneously, the diversification of financing based on type of contract, type of usage, and economic sector influence on ROA at the Islamic bank.Keywords: Diversification of financing based of economic sector, type of contract, type of usage, Return on Asset (ROA)